2020
DOI: 10.3389/fcell.2020.572182
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitofusins and Mitophagy in Life or Death Decisions

Abstract: Mitochondria entail an incredible dynamism in their morphology, impacting death signaling and selective elimination of the damaged organelles. In turn, by recycling the superfluous or malfunctioning mitochondria, mostly prevalent during aging, mitophagy contributes to maintain a healthy mitochondrial network. Mitofusins locate at the outer mitochondrial membrane and control the plastic behavior of mitochondria, by mediating fusion events. Besides deciding on mitochondrial interconnectivity, mitofusin 2 regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 320 publications
(425 reference statements)
1
30
0
Order By: Relevance
“…In the post-infarcted heart, liraglutide (a classical anti-diabetic drug) was found to reduce cardiac fibrosis, inhibit the inflammatory response, and prevent myocardial death by inhibiting Parkin-induced mitophagy ( Qiao et al, 2018 ). These findings suggest that excessive mitophagy can exacerbate cardiac injury ( Joaquim and Escobar-Henriques, 2020 ).…”
Section: The Dual Role Of Mitophagy In Myocardial Damagementioning
confidence: 99%
“…In the post-infarcted heart, liraglutide (a classical anti-diabetic drug) was found to reduce cardiac fibrosis, inhibit the inflammatory response, and prevent myocardial death by inhibiting Parkin-induced mitophagy ( Qiao et al, 2018 ). These findings suggest that excessive mitophagy can exacerbate cardiac injury ( Joaquim and Escobar-Henriques, 2020 ).…”
Section: The Dual Role Of Mitophagy In Myocardial Damagementioning
confidence: 99%
“…Among others, our previous finding evidenced a possible role of mitochondrial dynamics in the control of cellular health and functionality in different tissues [55,80], suggesting the importance of studying these physiological mechanisms, mainly in the liver, that play a key role in lipid metabolism as well as in detoxification processes against external toxic agents [81]. We chose to analyze MFN2 because it has also been suggested that MFN2 is a protective target in the liver, as it controls the physiological balance between apoptosis and autophagy in liver failure [82]. As far as we know, this is the first time that mitochondrial proteins involved in mitochondrial dynamic behaviour are investigated in response to increasing doses of DDE in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our present data showed DHA pretreatment upregulated the protein levels of mitophagy-specific molecules in astrocytes at 12 hours after hypoxia, suggesting that the mitochondrial protection from ischemic/reperfusion stress by DHA is to some extent due to mitophagy enhancement. Another reactive mitochondrial quality control is reshaped by fusion and fission [ 34 , 40 ]. The result demonstrated an upregulation of mfn1 and mfn2 (mitofusin-specific protein), which indicated that DHA promoted mitochondrial fusion in the hypoxia-treated astrocytes.…”
Section: Discussionmentioning
confidence: 99%